Epidemiological characteristics of common respiratory infectious diseases in children before and during the COVID-19 epidemic - Wang, Bing; Gai, Xiangzhen; Han, Yuling; Liu, Yanqin; Zhang, Yun; Sun, Jing; Liu, Miao; Yu, Huafeng; Peng, Zhenju; Wei, Xiaoling; Chang, Yuna; Ma, Xiang; et al. (Frontiers in Pediatrics, 2023)
Background: Since the outbreak of coronavirus disease 2019 (COVID-19), public's awareness of infection prevention and control has increased overall, and various prevention and control measures have been adopted. These measures may also have a certain impact on the occurrence of other infectious diseases. Therefore, we collected information on children with several respiratory infectious diseases in Jinan Children’s Hospital in China from 2016 to 2022 and analyzed their changes. Method: We collected data on age, sex and number of cases of pertussis, measles, scarlet fever, pulmonary tuberculosis, mumps and influenza, which were diagnosed by clinical and laboratory criteria, from 1 January 2016 to 31 December 2022 in Jinan Children's Hospital in Jinan, Shandong Province, China. Data on the number of people affected by these diseases in China from the Chinese Center for Disease Control and Prevention were compared. Then, we processed the data by using WPS Excel 2019 and SPSS. Results: A total of 12225 cases were included in this study in Jinan Children’s Hospital, which consisted of 3688 cases of pertussis (2200 cases before COVID-19 and 1488 during COVID-19), 680 cases of measles (650 cases before COVID-19 and 30 during COVID-19), 4688 cases of scarlet fever (4001 cases before COVID-19 and 687 during COVID-19), 114 cases of tuberculosis (86 cases before COVID-19 and 28 during COVID-19), 449 cases of mumps (340 cases before COVID-19 and 109 during COVID-19) and 2606 cases of influenza (1051 cases before COVID-19 and 1555 during COVID-19). The numbers of children in the hospital with pertussis, measles, scarlet fever, mumps and influenza decreased substantially during COVID-19 in 2020-2022 compared with numbers in 2016-2019, while numbers of patients in China with all six respiratory infectious diseases, including pulmonary tuberculosis, declined during the pandemic. A rebound of pertussis, scarlet fever and influenza was observed in 2021 and 2022. Conclusions: The study found that viral pathogens such as those causing measles, mumps and influenza all decreased during the pandemic, after which influenza rebounded. Infection diseases caused by bacteria such as scarlet fever and pertussis also decreased during COVID-19, and then a rebound occurred. However, tuberculosis stayed relatively constant.